Stable isotopes reveal captive vs wild origin of illegally captured songbirds in France. (September 2019) - Jiguet, Frédéric; Kardynal, Kevin J.; Hobson, Keith A.
Highlights: Protected Ortolan Buntings are poached in France for gastronomic purposes. Captive-grown feathers of Ortolans had low deuterium concentrations. We observed variable proportions of wild buntings within seized birds. Stable isotopes are useful to infer wild vs. captive origin of seized birds. Abstract: Naturally occurring stable isotopes of several elements are important tracers in the study the wildlife ecology including the identification of origins for migration research, investigations of trophic relationships, and in the forensic determination of illegally harvested and captive fauna. Extensive illegal trapping for use as decoys and in cuisine has contributed to drastic declines of Ortolan Bunting Emberiza hortulana populations breeding and migrating through France. We contrasted feather hydrogen isotope ( δ 2 Hf ) values in illegally captured and subsequently confiscated Ortolan Buntings (n = 234), including feathers known to have grown in captivity (n = 34) or of unknown growing environment (wild or cage), with δ 2 Hf values in birds legally caught (ringed and released) in the wild (n = 40). We sought to determine if feathers from these bird groups could be differentiated based on this single isotope. Feathers grown in captivity had considerably lower δ 2 Hf relative to feathers of wild birds, which is potentially indicative of tap water consumption and the use of different diets in captive birds. Further, applying mixing models to δ 2 Hf values revealed similar proportions of captive vs. wild origins for birds illegally captured in 2012, 2014 and 2015, and a larger proportion of individuals with feathers grown in the wild in 2013. This potentially mirrors the confiscation of birds at poaching sites only in the former years, but also of recently caught wild buntings kept captive in 2013. Our results show that even a single stable isotope ( δ 2 H) with good association with origins where feather keratins are produced is potentially useful in understanding origins of captive birds and may advance the monitoring of illegally captured birds.